2021
DOI: 10.3389/fmed.2020.616578
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipidomics in Translational Sepsis Research–Biomedical Considerations and Perspectives

Abstract: Scientific Background: Sphingolipids are a highly diverse group of lipids with respect to physicochemical properties controlling either structure, distribution, or function, all of them regulating cellular response in health and disease. Mass spectrometry, on the other hand, is an analytical technique characterizing ionized molecules or fragments thereof by mass-to-charge ratios, which has been prosperingly developed for rapid and reliable qualitative and quantitative identification of lipid species. Parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 188 publications
(217 reference statements)
0
3
0
Order By: Relevance
“…SM (d18:0/16:1(9Z)) is a sphingolipid substance on the membranes of cells that contributes to the structural integrity of those cells. It is also an essential component of signal transduction modules of critical biological reactions, such as cell division, differentiation, gene expression, and apoptosis [ 21 , 22 ]. This work found that SM (d18:0/16:1(9Z)) levels decreased significantly in the sepsis group, consistent with the previous study by Winkler et al [ 23 ], concluding that SM (d18:0/16:1(9Z)) is an accurate predictor for septic mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…SM (d18:0/16:1(9Z)) is a sphingolipid substance on the membranes of cells that contributes to the structural integrity of those cells. It is also an essential component of signal transduction modules of critical biological reactions, such as cell division, differentiation, gene expression, and apoptosis [ 21 , 22 ]. This work found that SM (d18:0/16:1(9Z)) levels decreased significantly in the sepsis group, consistent with the previous study by Winkler et al [ 23 ], concluding that SM (d18:0/16:1(9Z)) is an accurate predictor for septic mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the rapid, reliable, and high sensitivity, specificity, and throughput properties of LC-MS, it is possible to characterize the sphingolipidome of large-scale clinical samples, resulting in a systemic overview of the dynamic host-parasite interaction and recognition of the SPLs that mediate pathological processes ( Lee et al., 2014 ; Chong et al., 2018 ; Thu et al., 2020 ). Several studies have reviewed the important role of SPLs in the progression of infection ( Hanada, 2005 ; Maceyka and Spiegel, 2014 ; Chong et al., 2018 ; Li et al., 2019 ; Claus and Graeler, 2020 ). For instance, elevated plasma levels of SM (d18:0/16:0), SM (d18:1/16:0) and three glycosphingolipids were observed in CAP patients ( To et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the physiological and pathological roles of SPLs as pathogenetic elements or biomarkers of diseases were also reviewed in previous studies ( Matanes et al., 2019 ; Iessi et al., 2020 ). Due to its high sensitivity, specificity and throughput, as well as being rapid and reliable, SPL analysis by liquid chromatography-mass spectrometry (LC-MS) has become the most powerful strategy ( Becker et al., 2018 ; Claus and Graeler, 2020 ) and has been employed in discovery of biomarkers of various diseases. For instance, we discovered the characteristic SPLs that could be used as diagnostic biomarkers to differentiate different types of polycystic ovary syndrome (PCOS) in our previous study ( Li et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%